Buy-back and revenue-sharing contracts in global supply chain - Yang Liu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The main propose of this study is to investigate how exchange rate risk affects the buy-back and revenue-sharing contracts in the global supply chain, hence to improve the performance of global supply chain. Design/methodology/approach: Based on a two-echelon global supply chain, with the model equilibrium, this paper studies the difference between the buy-back contract and the revenue-sharing contract. By the transmitting of the exchange rate risk, it discusses the nodeenterprises' optimal strategies. Findings: The result shows that: (1) Both these two contracts can diminish the inefficiency caused by demand risk, but none of them can manage the exchange rate risk. (2) No matter which currency is used to settle the payment, both these two contracts will lead to the transmitting of exchange rate risk from one node-enterprise to another. (3) When the currency of the supplier's country in the relatively appreciating, it is better to use the buy-back contract; when the currency of the supplier's country in the relatively depreciating, the revenue-sharing contract will lead to a better result. Research limitations/implications: Though this study analyzes how the exchange rate risk affects these two contracts, it based on the assumption that node-enterprises' goal is maximizing theirs expected profit. In fact, many firms not only focus on maximizing theirs expected profit; the risk-taking is also an important concern. For future researches, how firms' risk-preferences affects theirs decisions in the global supply chain will be an interesting question. Also, will there be any difference if consider the node-enterprises' utility functions instead of the expected profit. Originality/value: Existing literature about the global supply chain mainly focus on the exchange rate risk management, few of them considers the double marginalization effect caused by the demand risk. Therefore, with the exchange rate fluctuation, we discuss the difference between the buy-back contract and the revenue-sharing contract.
Keywords: 650; global supply chain; exchange rate risk; buy-back contract; revenue-sharing contract